Math Problem Statement

Prove the following logical equivalences and simplify logical statements as given: 1. Prove that the following statements are equivalent: A. ¬(p ∧ ¬q) ∨ (¬p ∧ ¬q) ≡ ¬p B. ¬((¬p ∧ q) ∨ (¬p ∧ ¬q)) ∨ (P ∨ Q) ≡ P 2. Simplify the following using logical equivalence laws: A. ¬(¬p ∧ q) ∧ (p ∨ q) B. (p ∨ ¬q) ∧ ¬(p ∧ q)

Solution

Let's analyze and solve the given problems based on the uploaded image:

Problem 1: Proving Logical Equivalence

We have to prove the following statements:

A.

¬(p¬q)(¬p¬q)¬p\neg (p \land \neg q) \lor (\neg p \land \neg q) \equiv \neg p

Let's use logical equivalence steps:

  1. Apply De Morgan's Law: ¬(p¬q)=¬p¬(¬q)=¬pq\neg (p \land \neg q) = \neg p \lor \neg (\neg q) = \neg p \lor q Thus, the expression becomes: (¬pq)(¬p¬q)(\neg p \lor q) \lor (\neg p \land \neg q)
  2. Apply the Absorption Law: ¬p(¬p¬q)=¬p\neg p \lor (\neg p \land \neg q) = \neg p Therefore, ¬(p¬q)(¬p¬q)¬p\neg (p \land \neg q) \lor (\neg p \land \neg q) \equiv \neg p This verifies that statement A is correct.

B.

¬((¬pq)(¬p¬q))(PQ)P\neg ((\neg p \land q) \lor (\neg p \land \neg q)) \lor (P \lor Q) \equiv P

Let's simplify:

  1. Apply distribution: ¬p(q¬q)=¬pTrue=¬p\neg p \land (q \lor \neg q) = \neg p \land \text{True} = \neg p Thus, the original expression simplifies to: ¬(¬p)(PQ)p(PQ)\neg (\neg p) \lor (P \lor Q) \equiv p \lor (P \lor Q) By the idempotent law and identity laws, we get: pPPp \lor P \equiv P This verifies that statement B is also correct.

Problem 2: Simplifying Logical Statements

A.

¬(¬pq)(pq)\neg (\neg p \land q) \land (p \lor q)

Let's simplify it step-by-step:

  1. Apply De Morgan's Law: ¬(¬pq)=p¬q\neg (\neg p \land q) = p \lor \neg q The expression becomes: (p¬q)(pq)(p \lor \neg q) \land (p \lor q)
  2. Apply distribution: p(¬qq)=pFalse=pp \lor (\neg q \land q) = p \lor \text{False} = p Hence, the entire expression simplifies to: pp

B.

(p¬q)¬(pq)(p \lor \neg q) \land \neg (p \land q)

Let's simplify:

  1. Apply De Morgan's Law: ¬(pq)=¬p¬q\neg (p \land q) = \neg p \lor \neg q The expression becomes: (p¬q)(¬p¬q)(p \lor \neg q) \land (\neg p \lor \neg q)
  2. Apply distribution: (p¬p)(p¬q)(¬q¬q)(p \land \neg p) \lor (p \land \neg q) \lor (\neg q \land \neg q) The simplified expression is: p¬qp \land \neg q

Final Results

  1. For Problem 1:

    • A: ¬(p¬q)(¬p¬q)¬p\neg (p \land \neg q) \lor (\neg p \land \neg q) \equiv \neg p
    • B: ¬((¬pq)(¬p¬q))(PQ)P\neg ((\neg p \land q) \lor (\neg p \land \neg q)) \lor (P \lor Q) \equiv P
  2. For Problem 2:

    • A: ¬(¬pq)(pq)p\neg (\neg p \land q) \land (p \lor q) \equiv p
    • B: (p¬q)¬(pq)p¬q(p \lor \neg q) \land \neg (p \land q) \equiv p \land \neg q

Would you like further details or explanations on any part?

5 Questions for Further Practice

  1. What is De Morgan's law, and how is it used in logical equivalence?
  2. Can you apply the absorption law to simplify other logical expressions?
  3. How does the distribution law work in logical equivalence?
  4. Can two different expressions be equivalent without using basic logical equivalences?
  5. How does using truth tables help verify logical equivalences?

Tip

When simplifying logical statements, always apply De Morgan's Law first to eliminate negations, making the remaining expressions easier to handle!

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Logical Equivalence
Propositional Logic
Boolean Algebra

Formulas

De Morgan's Law
Distribution Law
Absorption Law
Idempotent Law
Identity Law

Theorems

De Morgan's Theorem
Distribution Theorem
Absorption Theorem

Suitable Grade Level

Undergraduate (Computer Science/Logic courses)